"I was so worried about every drop of milk" – feeding problems at home are a significant concern for parents after major heart surgery in infancy. Issue 2 (19th February 2016) - Tregay, Jenifer; Brown, Katherine; Crowe, Sonya; Bull, Catherine; Knowles, Rachel; Wray, Jo
Abstract: Increasing numbers of operations in small infants with complex congenital heart disease are being carried out in the UK year on year, with more surviving the initial operation. However, even after successful surgery some of these infants remain fragile when they are discharged home. The aim of the study was to elicit parents' experiences of caring for a child with complex needs after major congenital heart surgery. We conducted a qualitative study involving semi‐structured interviews with parents of 20 children (aged <1–5 months at hospital discharge), who had undergone open heart surgery and subsequently died or been readmitted unexpectedly to intensive care following their initial discharge home. Feeding difficulties following discharge from the specialist surgical centre emerged as one of the most significant parental concerns spontaneously raised in interviews. For some parents the impact of feeding difficulties overshadowed any other cardiac concerns. Key themes centred around feeding management (particularly the practical challenges of feeding their baby), the emotional impact of feeding for parents and the support parents received or needed after discharge with respect to feeding. Caring for a child with congenital heart disease following surgery is demanding, with feeding difficulties being one of the most significant parent stressors. Local health professionals can be a good source of support for parents provided that they are well informed about the needs of a cardiac baby and have realistic expectations of weight gain. Specialist surgical centres should consider addressing issues of parental stress around feeding and weight gain prior to hospital discharge. © 2016 Blackwell Publishing Ltd